Association between cannabis use and schizotypal dimensions – A meta-analysis of cross-sectional studies - Szoke, Andrei; Galliot, Anne-Marie; Richard, Jean-Romain; Ferchiou, Aziz; Baudin, Grégoire; Leboyer, Marion; Schürhoff, Franck (Psychiatry research, 2014)
Cannabis consumption can cause abuse and dependence and increase risk of developing psychiatric and somatic disorders. Several literature reviews explored the link between cannabis consumption and schizophrenia but none summarized the rich literature on cannabis and psychometric schizotypy. The aim of our review is to synthesize data from studies that explored the association between cannabis consumption and schizoptypal dimensions. A systematic review of the literature and, when needed, contact with the authors, allowed us to gather data from 29 cross-sectional studies. We compared schizotypy scores between subjects that never used cannabis and subjects that used it at least once (“never vs. ever”) and between current users and subjects that do not use cannabis currently (“current vs. other”). We conducted separate analyses for total schizotypy score and each of the three classical schizotypal dimensions (positive, negative, disorganized). For all eight comparisons, the cannabis group (“ever” or “current”) had higher schizotypy scores. Differences were in the small or medium range and, with the exception of the negative score in the current vs. other comparison, statistically significant. Cannabis consumption is associated with increased schizotypal traits. More research, using different approaches (e.g. longitudinal studies) is needed to explore the cause of this association.